2015
DOI: 10.1016/j.jnutbio.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Low level of trans-10, cis-12 conjugated linoleic acid decreases adiposity and increases browning independent of inflammatory signaling in overweight Sv129 mice

Abstract: The objective of this study was to determine the extent to which a low level of trans-10, cis-12 (10,12) conjugated linoleic acid (CLA) decreases adiposity and increases browning in overweight mice, its dependence on inflammatory signaling, and potential synergistic effects of daily exercise. Young, Sv129 male mice were fed a high fat diet for 5 wk to make them fat and glucose intolerant, and then switch them to a low fat diet with or without 0.1% 10,12 CLA, sodium salicylate, or exercise for another 7 wk. 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 40 publications
3
36
1
Order By: Relevance
“…Our studies confirm and extend previous reports that 10,12 CLA is associated with browning of WAT [ 11 , 62 ]. Moreover, 10,12 CLA failed to activate BAT (assessed by Ucp1 mRNA and protein levels), also consistent with previous findings [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our studies confirm and extend previous reports that 10,12 CLA is associated with browning of WAT [ 11 , 62 ]. Moreover, 10,12 CLA failed to activate BAT (assessed by Ucp1 mRNA and protein levels), also consistent with previous findings [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous evidence suggests that weight loss induced by 10,12 CLA in mice [ 11 ] and humans [ 12 ] is accompanied by increased adipose tissue fatty acid oxidation (FAO), a lipid catabolic pathway uncommonly used by adipocytes. In striking contrast to the lipogenic effects of other fatty acids such as palmitate and 9,11 CLA, we and others have shown that cultured adipocytes treated with 10,12 CLA display a pro-inflammatory phenotype with increased mitochondrial respiration and FAO [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is growing evidence showing that conjugated linoleic acid (CLA), either trans-10 or cis-12 isomer alone, or the mixture with cis-9 and trans-11 isomer, increases the thermogenic activity in the adipose tissue [35][36][37]. The thermogenic action of CLA is most evident in the WAT with a minor impact on the BAT [37]. It is quite distinctive from the thermogenic activity exerted by ALA enrichment in this work, since n3Bu supplementation promotes thermogenesis in the BAT, while causes a minimal impact on the WAT.…”
Section: Discussionmentioning
confidence: 99%
“…CLA led to reduction in percentage of body fat, and increased UCP1 level and fatty acid oxidation 117. , 118. 12,13-Dihydroxy-9 Z -octadecenoic acid (12,13-diHOME), a lipid to stimulate BAT activity, is negatively correlated with body-mass index.…”
Section: Miscellaneousmentioning
confidence: 99%